Comparación de cuatro métodos para contar peces en una bahía tropical: el caso del Área Marina de Manejo Bahía Santa Elena en el Pacífico de Costa Rica - Espinoza, Mario (2022)
Introduction: Tropical nature is experiencing an unprecedented threat that includes coastal fish communities that requires a close monitoring of species presence. The simultaneous use of several monitoring methods should reduce the bias caused by the selectivity of each method. Objective: This study used four different sampling methods over two years to assess and compare fish assemblages in the Santa Elena Bay Marine Management Area (AMM-BSE), North Pacific of Costa Rica. Methods: We examined changes in species richness and composition between upwelling and non-upwelling seasons from July 2019 and February 2020. We applied visual censuses, underwater remote cameras; bottom lines; and sport fishing. Results: We identified 140 species of fish (54 families); remote underwater cameras detected 83 %, followed by underwater visual censuses (65 %), sport-fishing (16 %) and bottom lines (14 %). Only the sport-fishing method detected differences in species richness and composition between seasons. Conclusion: Remote cameras appear to be the best method for species counts, and sport-fishing to detect seasonal differences in tropical coasts similar to the one studied here.